Steering Problem Solving Between Cliff Incoherence and Cliff Solitude - Meheus, Joke; Batens, Diderik (Philosophica, 1996)
Starting from Nickles' constraint-inclusion model, we present five challenges that any rational problem solving model should meet, but that seem to lead to an inextricable riddle. We then introduce the contextual model and show, step by step, that it meets all the challenges and resolves the riddle. This results in a strong argument for the concept of rationality that underlies the model.
Appeared 1998